An Effective Algorithm For Image Compression Using SCWP (International Journal of Engineering and Computer Science, 2017)
In the conventional sub band /wavelet decomposition is performed on the spatial-domain image. But here may be using a decomposition Technique where the sub band decomposition is performed on the global DCT spectrum of the image. That is, the two-dimensional spectrum rather than the image   is represented by a sum of basis functions, each weighted by the transform coefficients. The spectral sub band decomposition is then used as the basis for a new image coder, building on the spectral condensed wavelet packet (SCWP) algorithm. Ironically, this method is may expected to have lower arithmetic complexity than conventional sub band/wavelet coders that directly decompose a time or spatial domain signal. This new method may have lower complexity and higher compression performance.image coding, the sub band